2002
DOI: 10.1002/sia.1418
|View full text |Cite
|
Sign up to set email alerts
|

In situ interfacial analysis of evaporated potassium on the electroluminescent fluorene–thiophene copolymer

Abstract: X-ray photoelectron spectroscopy (XPS) was used to investigate the interface formation during in situ thermal evaporation of potassium on thin films of an electroluminescent conjugated polymer: poly[2,7-(9,9-dihexylfluorene)-co-alt-2,5-(decylthiophene)] (PFT). The chemical state and composition of the metal/polymer interfaces were studied as a function of the potassium coverage. Potassium was found to interact extensively with the bulk-adsorbed oxygen to form a layer of metal oxide at the K/PFT interface. Migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The presence of PEG at the organic/metal interface is associated with the C-O peak at 286.6 eV in the XPS spectrum which is characteristic of the pristine PEG in the C1s XPS spectrum. 36 The peak at 286.6 eV binding energy could also be attributed to the interaction of Al atoms with bulk adsorbed oxygen and the polymer to form an Al-O-C complex, [37][38][39] or due to organic contaminants adsorbed on the sample's surface. The contribution of these species is represented in the intensity of the C-O peak in the XPS spectra of pristine P3HT lms with no PEG.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of PEG at the organic/metal interface is associated with the C-O peak at 286.6 eV in the XPS spectrum which is characteristic of the pristine PEG in the C1s XPS spectrum. 36 The peak at 286.6 eV binding energy could also be attributed to the interaction of Al atoms with bulk adsorbed oxygen and the polymer to form an Al-O-C complex, [37][38][39] or due to organic contaminants adsorbed on the sample's surface. The contribution of these species is represented in the intensity of the C-O peak in the XPS spectra of pristine P3HT lms with no PEG.…”
Section: Resultsmentioning
confidence: 99%
“…Al-O-C species have been widely reported in works involving Al and Al 2 O 3 /polymer interfaces. The location of Al-O-C species in comparison with the neutral hydrocarbon (lower or higher) differed from one author to another [34,[59][60][61][62][63][64][65][66]. It is reasonable to suggest that there are two types of Metal-O-C species.…”
Section: Characterisation Of the Zinc Oxide/pet Interfacementioning
confidence: 86%
“…It has been also reported that the Al metal can effectively transfer the electron to the conjugated polymer with the sulde species, and this feature makes it a potential cathode for polymeric electronics. 39 Another study 40 has also reported that Cu can react with P3HT and form sulde like species. These sulde like species can improve the solar cell performance.…”
Section: Discussionmentioning
confidence: 99%